Penyusunan Rancangan Standar Operasional Prosedur (SOP) Mekanisme Uang Persediaan (UP) pada Sekretariat Kementerian Kependudukan dan Pembangunan Keluarga/BKKBN - Nabila Eka Fitriani; Hera Khairunnisa; Ratna Anggraini (Indo Publishing, 2025)
This study selected the Secretariat of the Ministry of Population and Family Development/National Population and Family Planning Board (Kemendukbangga/BKKBN) as the research site because no Standard Operating Procedure (SOP) governing Cash Advance Mechanism currently exists within its operations. The absence of such an SOP may compromise the integrity of state finances and increase financial risks, including administrative errors and other irregularities. Therefore, this research aims to develop a systematic, clear, and regulation-compliant draft SOP for Cash Advance and Revolving Cash Advance requests within the Secretariat of the Ministry of Population and Family Development/BKKBN. Additionally, the study seeks to obtain validation of the developed SOP draft. Developing this SOP draft is crucial as it will serve as a practical guideline for employees in carrying out their duties, thereby supporting the achievement of government objectives and targets. The study employed a qualitative descriptive method, complemented by the ADDIE (Analysis, Design, Development, Impelementation, and Evaluation) model to ensure the resulting output is both approriate and practical. Data were collected through observation, interviews, and documentation. The research produced a draft SOP for the Cash Advance mechanism, specifically covering Cash Advance and Revolving of Cash Advance procedures. This draft was developed in accordance with the provisions of the Minister of Finance Regulation No. 62 of 2023 on Budget Planning, Budget Implementation, and Financial Accounting and Reporting, as amended by PMK No. 107 of 2024. The draft SOP was validated by an informant who serves as a functional treasury officer at the working unit, confirming that the SOP is valid, compliant with appicable regulations, and aligned with the unit’s operational needs.